The Effect of Self‐Compassion Distant Education on Depression in Pregnant Women: A Randomized Clinical Trial - Bita Ashabi; Nader Salari; Nasrin Jaberghaderi; Mastaneh Kamravamanesh (Health Science Reports, 2025)
ABSTRACT Background Depression is the most prevalent mental disorder that arises during pregnancy. Maternal depression impacts the health and development of the baby and can have negative effects on the mental health of future generations. The most effective method for addressing this disorder is through the teaching of psychological approaches, so this study was conducted with the aim of determining the effect of remote self‐compassion training on depression in pregnant women. Methods In this randomized clinical trial study, 72 pregnant mothers with depressive symptoms (36 in the control group and 36 in the intervention group), referred to the comprehensive health service centers of Kermanshah city, Iran, were selected by available sampling method(s). To collect information in three stages before the training, 1 week and 1 month after the training, the Edinburgh Depression Questionnaire and the Short Form Self‐Compassion Questionnaire were used. Both groups received the centers' usual care, and the intervention group received self‐compassion distance training in addition to the usual care of the centers. The intervention group also received 8 self‐compassion distance training sessions (30–40 min each session). Results The findings showed that before the intervention, the two groups did not have a statistically significant difference in terms of depression scores. Teaching self‐compassion to pregnant women caused a significant decrease in depression (p < 0.05), and there was a significant difference between the two groups (p < 0.05). Conclusion Remote self‐compassion training improved the symptoms of depression during pregnancy; therefore, according to the need of these women to improve their mental health and reduce the adverse consequences of depression, using this type of educational approach in health centers can be useful. Trial Registration Iranian Registry of Clinical Trials (IRCT): IRCT20130812014333N174.